A sense-making approach to pre-service teachers’ use of teaching and learning materials in resource-constrained contexts. - Maxwell Tsoka (Nurul Jadid University, 2026)
This study examines how prospective teachers understand and use teaching and learning materials in the context of under-resourced schools. The goal is to uncover how the sense-making process influences pedagogical decisions when teaching. The research used a phenomenological approach with classroom observation and in-depth interviews with one prospective teacher who taught the topic of electrical circuits in grade 9. Thematic analysis is used to identify patterns of use of teaching materials and the way prospective teachers interpret their functions. The results showed that the selection of teaching materials was driven by personal experience and peer recommendations, rather than mature pedagogical considerations. The implementation of the material in the form of videos takes place passively without activities that encourage student involvement. Prospective teachers are not able to connect teaching tools with learning objectives so that the potential of the material is not utilized optimally. The discussion highlighted that limited sense-making has an impact on the quality of learning and hinders the development of professional competencies. The findings of the study suggest the need for professional learning communities to strengthen the pedagogical reflection and understanding of prospective teachers. This study shows that structured support can improve the ability to use teaching materials effectively in the context of limitations.